Individual Specialization - Costa-Pereira, Raul; Araújo, Márcio S. [UNESP] (Elsevier, 2024)
Natural populations are collections of ecologically diverse individuals, which are often specialized in small subsets of the population niche. Nearly two decades after the concept of individual specialization was formally coined, accumulated evidence confirms that this phenomenon is prevalent in nature across a myriad of taxa and has major ecological, evolutionary, and conservation implications. Ecologists now possess a diverse toolbox of methods to quantify niches at the scale of individuals with unprecedented accuracy. Despite recent advances on the relevance of individual specialization for higher levels of biological organization (e.g., populations, communities), key questions about its causes and consequences remain unanswered.
Keywords: Diet; Fitness; Functional trade-offs; Individual ecology; Individual variation; Intraspecific diversity; Intraspecific variation; Isotopic niche; Niche overlap; Niche space; Niche variation; Niche width; Resource use; Stable isotopes; Trophic niche